Propagation of femtosecond pulses in a hollow-core revolver fibre. (July 2016) - Yatsenko, Yu.P.; Krylov, A.A.; Pryamikov, A.D.; Kosolapov, A.F.; Kolyadin, A.N.; Gladyshev, A.V.; Bufetov, I.A.
Abstract: We have studied for the first time the propagation of femtosecond pulses through an optical fibre with an air-filled hollow core and a cladding in the form of one ring of noncontacting cylindrical capillaries for high-power radiation transmission in the telecom range. Numerical analysis results demonstrate that the parameters of the fibre enable radiation transmission in the form of megawatt-power Raman solitons through up to a length of the fibre and tuning of the emission wavelength over . We have experimentally demonstrated femtosecond pulse transmission through fibres up to in length in the linear propagation regime, without distortions of the pulse spectrum, with a dispersion-induced temporal pulse broadening within 20 %.